Coronaviral Infection (COVID-19) in Children (Situation on April 2020) - Leyla S. Namazova-Baranova (Union of pediatricians of Russia, 2020)
Dear friends, colleagues!Not so much time has passed since my last published review on this topic, bit so many news has appeared that has completely changed our vision of the disease and its treatment! It is interesting in both, medical and philosophical way. From philosophical point of view: 1-2 months of our previous pre-COVID life flew quick as lightning but now it is long period while we are observing this new infection and looking for new ways of management and its control. Then as now we are going to discuss its medical part.